2013
DOI: 10.1038/srep02767
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Protection of Ischemic Myocardium by FGF21 from the Liver and Adipose Tissue

Abstract: Myocardial ischemia, while causing cardiomyocyte injury, can activate innate protective processes, enhancing myocardial tolerance to ischemia. Such processes are present in not only the heart, but also remote organs. In this investigation, we demonstrated a cardioprotective process involving FGF21 from the liver and adipose tissue. In response to myocardial ischemia/reperfusion injury in the mouse, FGF21 was upregulated and released from the hepatic cells and adipocytes into the circulation and interacted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
132
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(138 citation statements)
references
References 61 publications
5
132
0
Order By: Relevance
“…The present study implies that the prevention of palmitate-induced cardiac apoptosis by FGF21 may partially depend on Akt. Our findings not only support previous studies showing that FGF21-mediated cardiac protection against ischaemia/ reperfusion injury is mediated by PI3K/Akt cell survival signalling under both in vitro and in vivo conditions [18,19], but also further establish FGF21-mediated cardiac protection against diabetic pathogenic changes via upregulation of ERK1/2-p38 MAPK-AMPK-mediated cell survival pathways.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The present study implies that the prevention of palmitate-induced cardiac apoptosis by FGF21 may partially depend on Akt. Our findings not only support previous studies showing that FGF21-mediated cardiac protection against ischaemia/ reperfusion injury is mediated by PI3K/Akt cell survival signalling under both in vitro and in vivo conditions [18,19], but also further establish FGF21-mediated cardiac protection against diabetic pathogenic changes via upregulation of ERK1/2-p38 MAPK-AMPK-mediated cell survival pathways.…”
Section: Discussionsupporting
confidence: 79%
“…Here, we provide direct evidence for the anti-apoptotic effect of FGF21 in cardiac tissue, with protection against palmitate in the cultured cardiac cell line and primary cardiomyocytes and STZ-induced diabetes or NEFA infusion in mice. We have also demonstrated that FGF21 supplementation prevents the progression of diabetes-induced cardiomyopathy in both WT and Fgf21-KO mice, a finding that is supportive of previous studies showing FGF21 protects against myocardial ischaemia/reperfusion injury [18,19] and isoprenalineinduced cardiac hypertrophy [20].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In response to myocardial ischemia in mice, both hepatic and adipocyte‐derived FGF21 expression and secretion were shown to be upregulated, highlighting a cardioprotective response of FGF21 in an endocrine manner 33. Recently, both cardiac FGF21 expression and secretion were also found to be increased significantly with isoproterenol treatment in mice and phenylephrine treatment in neonatal cardiomyocytes, respectively 30.…”
Section: Discussionmentioning
confidence: 99%